2020
DOI: 10.1038/s41597-020-0540-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal force and motion in collective cell migration

Abstract: Cells move in collective groups in biological processes such as wound healing, morphogenesis, and cancer metastasis. How active cell forces produce the motion in collective cell migration is still unclear. Many theoretical models have been introduced to elucidate the relationship between the cell's active forces and different observations about the collective motion such as collective swirls, oscillations, and rearrangements. though many models share the common feature of balancing forces in the cell layer, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 38 publications
(80 reference statements)
2
25
0
Order By: Relevance
“…Polyacrylamide substrates were prepared for traction force microscopy as described above but with the addition of 0.2 µm fluorescent particles (Dark Red 660/680, Fluospheres, Thermo Fisher Scientific). During gel polymerization, the gels were centrifuged upside down to localize the particles to the top as described in our prior work 57 , 58 . The traction experiments were performed with the cells expressing red fluorescent protein in their nuclei.…”
Section: Methodsmentioning
confidence: 99%
“…Polyacrylamide substrates were prepared for traction force microscopy as described above but with the addition of 0.2 µm fluorescent particles (Dark Red 660/680, Fluospheres, Thermo Fisher Scientific). During gel polymerization, the gels were centrifuged upside down to localize the particles to the top as described in our prior work 57 , 58 . The traction experiments were performed with the cells expressing red fluorescent protein in their nuclei.…”
Section: Methodsmentioning
confidence: 99%
“…An alternative explanation is that the treatments affected pack size by altering the distance over which cell-cell forces propagate. To consider this explanation, we quantified propagation of tensile stresses in the monolayer by using monolayer stress microscopy [24,51,52] and computing an autocorrelation. Results showed that the correlation length of tension was not statistically affected by treatment with JSP (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To examine the effects of 2D-packing on cell geometry, we used a dataset where the biophysical dynamics of collective migration were studied on confined PolyDiMethylSiloxane (PDMS) islands 24 . Data were extracted for MDCK cells subject to three experimental setups viz ., cytochalasin ‘D’ treatment (CytoD), high cell density (High) and low cell density (Low).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike published studies, our pipeline can be applied not only to scratch assay but also data from confluent monolayers and individual cells. The Saraswathibhatla et al ., and Zaritsky et al ., datasets were two such distinct studies which upon CGF analysis allowed us to speculate the role of 2D-packing on migratory heterogeneity 24,25 . While we cannot ignore the cell and experimental system specific effects, these trends between migratory subsets do recapitulate jamming-unjamming transitions which are reported during tissue development and disease progression 8,39,40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation